Labour Outcome in Adolescent Pregnancy (Journal of Chittagong Medical College Teachers' Association, 2014)
Adolescent pregnancy is associated with increased risk of developing complications in both adolescent mother and neonates. It may lead to significant maternal and perinatal mortality and morbidity. To evaluate the labour outcome in adolescent and adult mothers' immediately after delivery and compare the result. A cross sectional comparative study was performed over a period of one year (September 2009- August 2010) at the obstetrics department of Chittagong Medical College Hospital. Consecutive three hundred pregnant mothers admitted for delivery that was fulfilled the inclusion criteria included in study group. Among them 150 were adolescent (13-19yrs) belongs to group A and 150 was adult (20-29 yrs) belongs to group B. Labour outcome (prolonged or obstructed, mode of delivery, stillbirth, birth weight and birth asphyxia were recorded on a preformed questionnaire and statistical analysis done by using SPSS package for windows version 12. Adolescent mother has significant lower mean age at delivery than adults (18.61872 vs. 23.87 = 2.8 yrs. P< 001).Antenatal check up were also (10% vs. 26%, P < 001) infrequent in them. Spontaneous vaginal delivery significantly less (34.7% vs. 48%, P